Interleukin-1 is associated with inflammation and structural lung disease in young children with cystic fibrosis - Montgomery, S.T.; Dittrich, A.S.; Garratt, L.W.; Turkovic, L.; Frey, D.L.; Stick, S.M.; Mall, M.A.; Kicic, Anthony (ELSEVIER SCIENCE BV, 2018)
© 2018 European Cystic Fibrosis Society Background: Little is known about the role of interleukin (IL)-1 in the pathogenesis of cystic fibrosis (CF) lung disease. This study investigated the relationship between IL-1 signalling, neutrophilic inflammation and structural lung changes in children with CF. Methods: Bronchoalveolar lavage fluid (BALf) from 102 children with CF were used to determine IL-1α, IL-1β, IL-8 levels and neutrophil elastase (NE) activity, which were then correlated to structural lung changes observed on chest computed tomography (CT) scans. Results: IL-1α and IL-1β were detectable in BAL in absence of infection, increased in the presence of bacterial infection and correlated with IL-8 (p < 0.0001), neutrophils (p < 0.0001) and NE activity (p < 0.01 and p < 0.001). IL-1α had the strongest association with structural lung disease (p < 0.01) in the absence of infection (uninfected: p < 0.01 vs. infected: p = 0.122). Conclusion: Our data associates IL-1α with early structural lung damage in CF and suggests this pathway as a novel anti-inflammatory target.